Superconductivity at 7.3 K in Ti2InN - Bortolozo, A.D. (2010)
In this work the Ti2InN phase is investigated by X-ray diffraction, magnetic and resistivity measurements. X-ray powder patterns suggest that all peaks can be indexed with the hexagonal phase of Cr2AlC prototype. Electrical resistance as a function of temperature reveals superconductivity below 7.3 M(H) hysteresis loops show typical type-II superconductivity. Using R(H) versus T measurements we estimated muoHc2.0=10,8 T and e0= 55,2 Å. The results show unambiguously that Ti2InN is the first nitride superconductor belonging to the MnC1AXn family.